2019
DOI: 10.1002/wer.1105
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of different forms of phosphorus on modified corn bracts

Abstract: Excessive phosphorus discharged into the environment could result in the eutrophication, leading to water pollution. Hence, the efficient method for phosphorus removal is urgently in need. In this paper, an agricultural by‐product, corn bract, modified by Zr was proposed to remove different forms of phosphorus. A comparison study about the adsorption performance of organic phosphorus (OP) and inorganic phosphorus (IP) was investigated. The results indicated that both the OP and IP reached the maximum adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…The choice of these two ions was closely aligned with our primary objective: to use a natural, or develop a modified, sorbent to apply directly in agriculture practices. This application needed to be achieved without introducing additional substances, and in every case without leaving residues from the modifying treatment that could pollute the soil or cause undesirable effects on plant growth (an example being the use of zirconium as a bridge between natural biomass and phosphate [ 6 ]). The Ca-enriched biomass, in contact with H 2 PO 4 − fails to establish chemical-physical interaction, which is what happens between Ca and HPO 4 2− ions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of these two ions was closely aligned with our primary objective: to use a natural, or develop a modified, sorbent to apply directly in agriculture practices. This application needed to be achieved without introducing additional substances, and in every case without leaving residues from the modifying treatment that could pollute the soil or cause undesirable effects on plant growth (an example being the use of zirconium as a bridge between natural biomass and phosphate [ 6 ]). The Ca-enriched biomass, in contact with H 2 PO 4 − fails to establish chemical-physical interaction, which is what happens between Ca and HPO 4 2− ions.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches aim to maximize the utility of waste materials while ensuring sustainable P management [ 5 ]. Numerous studies have explored the capacity of various biomass adsorbents, including corn bracts [ 6 , 7 ], sugar cane bagasse [ 8 ] and wheat straw [ 9 ], dried cactus pear pruning [ 10 , 11 ]. Currently, cactus pear thrives in semi-arid regions across the globe and finds significant cultivation in the Mediterranean basin and Central America.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate adsorption usually reaches an optimal level when the pH promotes its electrostatic attraction to the adsorbent, i.e., when the pH of the solution is lower than that of the zero-charge point (ZPC) of the adsorbent, making it electropositive. Since several adsorbents have a ZPC near-neutral pH, optimal P adsorption is often in the acidic range [73][74][75][76][77][78][79].…”
Section: P Adsorptionmentioning
confidence: 99%
“…Using vegetable material (corn bracts) modified by zirconium (Zr), Jiang et al [79] observed an adsorption rate of organic P faster than that of inorganic phosphorus. Complexation and electrostatic attraction were probably the main adsorption mechanisms.…”
Section: P-adsorbent Bio-based Materials: "Green Removal"mentioning
confidence: 99%
“…Several methods to remove phosphate from water have been investigated in recent decades. The methods mainly include biological, phytoremediation, precipitation, and adsorption. , Among them, adsorption presents a low cost associated with high flexibility, design simplicity, and selectivity, making it ideal for sustainable phosphorus removal from effluents. ,, Unlike other techniques, it is also an excellent treatment for water contaminated with low phosphate levels since environmentally relevant phosphate concentrations range from trace levels to a few milligrams per liter. Bacelo et al reviewed many materials such as metal oxides/hydroxides, carbonate minerals, clay minerals, zeolites, porous silica, activated carbon, biochar, polymers, bioderived materials, and industrial waste that have been used in the adsorption of phosphate.…”
Section: Introductionmentioning
confidence: 99%